Preemptive use of oral gabapentin or pregabalin for acute postoperative pain following lower limb orthopaedic surgery under spinal anaesthesia - Acharya, Utsav; Ghimire, Aashish; Bhattarai, Balkrishna; Singh, Satyendra Narayan; Prasad, Jagat Narayan; Maharjan, Rajiv (Journal of Kathmandu Medical College, 2019)
Background: Postoperative pain is a major cause of perioperative morbidity and functional impairment. Preemptive analgesia is an analgesia regimen instituted before the surgery, to desensitize the pain pathways. Pregabalin and gabapentin have been claimed to be effective in reducing postoperative pain without significant alterations in hemodynamics. Objectives: This study was conducted to compare the effectiveness of pregabalin and gabapentin in reducing postoperative pain, total opioid consumption, postoperative nausea and vomiting and sedation in patients undergoing lower limb orthopaedic surgeries under spinal anaesthesia. Methodology: Eighty patients undergoing lower limb orthopaedic surgeries under spinal anaesthesia were divided into two groups, to either receive 300mg gabapentin or 150mg pregabalin, one hour before surgery. The patients were evaluated at one, two, six, 12 and 24 hours postoperatively and Visual Analogue Scale score for pain, postoperative nausea vomiting, and sedation score were monitored. Tramadol 50 mg was used as rescue analgesic and total consumption over 24 hours was recorded. Results: The mean duration of postoperative analgesia was significantly higher with pregabalin (282±106 minutes versus 234 ± 97minutes, p=0.009). The sedation score was significantly higher with pregabalin in the first hour (p=0.001). The total tramadol consumption was higher with gabapentin; however, it was statistically insignificant. The occurrence of postoperative nausea and vomiting was comparable between the groups. Minor adverse effects such as dizziness, sedation and headache were observed in both groups. Conclusion: Pregabalin 150 mg orally significantly increases the duration of postoperative analgesia than gabapentin 300mg following lower limb orthopaedic surgeries. Although sedation is frequently observed, it doesn’t alter the hemodynamics and thus, may be used safely.